1990
DOI: 10.1080/00288233.1990.10430660
|View full text |Cite
|
Sign up to set email alerts
|

Long-term selection for yearling weight or postweaning gain in Angus cattle

Abstract: Two selection herds with Angus cattle were maintained at Waikeria near Te Awamutu, New Zealand, from 1964 to 1981, with experimental calvings comprising 3355 recorded calves. The selection criterion was yearling weight in one herd (the YW herd) and postweaning weight gain in the other (the PWG herd). In the absence of a control herd, genetic responses were estimated using best linear unbiased prediction (BLUP) methods. Annual direct selection differentials averaged 6.45 kg in the YW herd and 5.00 kg in the PWG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Some studies have shown that maternal effects positively and significantly contributed to correlated responses in weaning and yearling weights (Herd, 1990;MacNeil et al, 1992;Koch et al, 1994), while other reports have shown marginal contribution (Carter et al, 1990;Morris et al, 1992). Arthur et al (1997) noted that the differences may partly be due to the absolute importance of maternal ability on expression of growth and partly due to the magnitude and sign of genetic correlations between direct and maternal effects.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that maternal effects positively and significantly contributed to correlated responses in weaning and yearling weights (Herd, 1990;MacNeil et al, 1992;Koch et al, 1994), while other reports have shown marginal contribution (Carter et al, 1990;Morris et al, 1992). Arthur et al (1997) noted that the differences may partly be due to the absolute importance of maternal ability on expression of growth and partly due to the magnitude and sign of genetic correlations between direct and maternal effects.…”
Section: Resultsmentioning
confidence: 99%
“…This created a gene pool from lines originally selected for increased growth in 1964-1981(Carter et al 1990). …”
Section: Methodsmentioning
confidence: 99%